Collective guidance at work : A resource for apprentices? - Filliettaz, Laurent [Verfasser] (My University, 2011)
"This article focuses on pedagogical aspects of initial vocational training in the context of the Swiss VET system. Even though apprentices are usually the responsibility of one main supervisor within companies, a number of other colleagues, experts and fellow apprentices interact with them as they engage in productive tasks. In that context, the article examines how first-year apprentices are guided and supported by experienced workers in the workplace, and how this guidance and support are distributed collectively in work teams. Drawing on an ethnographic and discursive methodology borrowing concepts and tools from various trends in applied linguistics, the article analyses empirical material consisting of videotaped interactions between apprentices and workers recorded in productive conditions. Two case studies related to distinct workplaces are discussed. They illustrate contrasting conditions experienced by apprentices when joining the workplace and provide evidence for the configuring role of guidance and supervision in vocational learning. The findings suggest that particular attention should be given to the pedagogical quality of guidance in the workplace to improve the overall efficiency of the dual apprenticeship system and to foster smooth and consistent transitions into work experience for novice apprentices." (Autorenreferat, BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; L 2.3.2 Handlungs- & problemorientierte Methoden; L 5 Beratung & Orientierung; I 2.2.1 Westeuropa; Betriebliche Berufsausbildung; Lernen am Arbeitsplatz; Praktische Unterweisung; Supervision; Soziale Beziehungen; Schweiz